The Theories and Methodologies of Orientalists in The Study of Islam: A case of William Muir and His Application - Aliyu Kabir; Olodo , Mohammed Muneer’deen Al-Shafi’i; Ahmad Bazli Bin Shafie (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Orientalism refers to the study of the Eastern world. This movement explores the multiple interpretations of the term in relation to Eastern languages, literatures, civilizations and religions. Most of Orientalists have constantly distorted the image of Islam. Since the beginning of Islam, they have made no effort to shed light on the various aspects and facts of the life of the Prophet Muhammad (saw) as well as the life of Islam in general. As a result, they were unable to understand the basic message of Islam. Prominent in this effort stands William Muir (1819-1905). William Muir was a Scottish modern Christian scholar and orientalist who wrote a large number of books on Islamic studies. To fully understand a researcher’s intellectual contributions, it is necessary to properly examine his theories and methodologies he applied. The theories and methodologies of William Muir in studying Islam played an important role in the Muslim-Christian relation. Muslims and Christian generally believed that the expertise and contributions of Muir in the field of Islamic studies cannot be overestimated. However, William Muir applied so many ways to gain the opportunity to acquire Islamic knowledge and to utilize that knowledge to criticize and condemn the Glorious Qur’an and the Prophethood of Muhammad (saw). The main objective of this paper is to provide the researcher with some essential information regarding Muir’s methodologies that may enable him to objectively analyse William Muir’s different opinions and ideas towards the Glorious Qur’an and the prophethood of Muhammad (saw). The finding shows that Muir applied five different methodologies in order to study Islam, namely Skepticism Method, Historico-critical Method, Epileptic Theory, The Theory of Judeo-Christian Origin of the Glorious Qur’an, and Subjective Approach. It has been shown that Muir’s theories and Methodology were greatly influenced by famous orientalists, such as Goldziher, Noldeke, Springer, and others. His choice of language has also been noted, as it has been shown that he used obscene and harsh words towards the Prophet (saw).